2009
DOI: 10.1093/ndt/gfp301
|View full text |Cite
|
Sign up to set email alerts
|

A cut-off value of plasma osteoprotegerin level may predict the presence of coronary artery calcifications in chronic kidney disease patients

Abstract: These results suggest that a CAC increase is strongly associated with a plasma OPG increase in CKD patients. The values of OPG >757.7 pg/mL allow us to predict the presence of CAC in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 48 publications
6
67
1
2
Order By: Relevance
“…Similar findings have been reported also in other cross-sectional and observational studies on HD patients (14,15). Additionally, the work by Moreno et al (16) showed that, among all risk factors examined, serum OPG level is the strongest predictor of CAC, and values of OPG.757.7 pg/ml (equivalent to 6.31 pmol/L) may predict the presence of CAC in CKD patients. Prospective and longitudinal studies investigating the effects of OPG/ RANKL axis on the progression of VC are scarce in the literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings have been reported also in other cross-sectional and observational studies on HD patients (14,15). Additionally, the work by Moreno et al (16) showed that, among all risk factors examined, serum OPG level is the strongest predictor of CAC, and values of OPG.757.7 pg/ml (equivalent to 6.31 pmol/L) may predict the presence of CAC in CKD patients. Prospective and longitudinal studies investigating the effects of OPG/ RANKL axis on the progression of VC are scarce in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…In cross-sectional observational studies, it was reported that high-serum OPG levels were associated with increased coronary artery calcification score (CACS) in patients with CKD (14)(15)(16). In two similar studies performed on renal transplant recipients, findings suggested a possible role of serum OPG on the progression of VC (17,18).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to our study, the AUC for CAC identification was 0.574 for fetuin A. In a study concerning CKD patients, osteoprotegerin had an AUC of 0.79 and neither of calcium phosphate disorder markers had similar ability (Morena et al 2009). …”
Section: Discussioncontrasting
confidence: 98%
“…The relation between coronary atherosclerosis and OPG has also been demonstrated in recent studies [4,18]. If atherosclerotic calcification fails, it can cause the vessels to break as a result of plaque rupture [4,19].…”
Section: Discussionmentioning
confidence: 72%
“…Also, we found a cutoff level of OPG in CAD. Morena et al [18] reported that the cutoff level of OPG was best able to predict the presence of significant CAD. But, the cutoff level of OPG could act as a predictor in CAD patients, since this attribute was found in chronic kidney disease patients.…”
Section: Discussionmentioning
confidence: 99%